2021
DOI: 10.1016/j.scitotenv.2021.147721
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-scale expanded assessment of inorganic and organic tapwater exposures and predicted effects in Puerto Rico, USA

Abstract: A pilot-scale expanded target assessment of mixtures of inorganic and organic contaminants in point-of-consumption drinking water (tapwater, TW) was conducted in Puerto Rico (PR) to continue to inform TW exposures and corresponding estimations of cumulative human-health risks across the US. In August 2018, a spatial synoptic pilot assessment of than 524 organic and 37 inorganic chemicals was conducted in 14 locations (7 home; 7 commercial) across PR. A follow-up 3-day temporal assessment of TW variability was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 141 publications
(229 reference statements)
8
32
0
Order By: Relevance
“…VOC remained a frequently detected class in public-supply TW locations, with predominantly xylenes observed in community C and xylenes and the fuel-oxygenate, t -butyl alcohol, systematically detected in community B. However, consistent with previous findings, 29 , 30 , 43 , 44 DBP dominated public supply organics, representing on average (median) 58% of detections and 92% of cumulative concentrations. Cumulative DBP concentrations were more than an order of magnitude higher ( p < 0.0001) in surface-water-sourced public-supply TW samples (community B only; median: 24.2 μg L –1 ) than in groundwater-sourced public-supply locations (median: 2.0 μg L –1 ) in communities B and C. Consistent with widespread agricultural use within Corn Belt drainage basins, 140 , 141 including the Missouri River basin, 142 pesticides (median: 6) were detected (concentrations ≤ 0.33 μg L –1 ) in every surface-water-sourced public-supply sample but were rarely detected in any groundwater-sourced location in this study.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…VOC remained a frequently detected class in public-supply TW locations, with predominantly xylenes observed in community C and xylenes and the fuel-oxygenate, t -butyl alcohol, systematically detected in community B. However, consistent with previous findings, 29 , 30 , 43 , 44 DBP dominated public supply organics, representing on average (median) 58% of detections and 92% of cumulative concentrations. Cumulative DBP concentrations were more than an order of magnitude higher ( p < 0.0001) in surface-water-sourced public-supply TW samples (community B only; median: 24.2 μg L –1 ) than in groundwater-sourced public-supply locations (median: 2.0 μg L –1 ) in communities B and C. Consistent with widespread agricultural use within Corn Belt drainage basins, 140 , 141 including the Missouri River basin, 142 pesticides (median: 6) were detected (concentrations ≤ 0.33 μg L –1 ) in every surface-water-sourced public-supply sample but were rarely detected in any groundwater-sourced location in this study.…”
Section: Resultssupporting
confidence: 87%
“…These results indicate that simultaneous exposures to contaminants of human-health interest are common in both public- and private-supply TW locations across the study area. The bioactivity-weighted screening (Σ EAR and Σ TQ ) results ( Tables S10 and S13 ) indicate that exposures to DBP and inorganics at <MCL concentrations are the primary drivers of human-health interest in public-supply TW in communities B and C. These public-supply results align with the previous findings 29 , 30 , 43 , 44 and support the need for better understanding of exposure-effect relations and cumulative health risks of regulated/unregulated DBP 152 , 154 and for improved source-water pretreatment technologies to address DBP precursors, such as surface-water natural organic matter. 156 , 163 Exposures to As and U in groundwater-sourced drinking-water supplies have been reported previously in the study area and the concentrations observed in public-supply TW herein were below corresponding NPDWR MCL.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations